2015
DOI: 10.1007/s00359-015-0997-4
|View full text |Cite
|
Sign up to set email alerts
|

Species-specificity of temporal processing in the auditory midbrain of gray treefrogs: interval-counting neurons

Abstract: Interval-counting neurons (ICNs) respond after a threshold number of sound pulses have occurred with specific intervals; a single aberrant interval can reset the counting process. Female gray treefrogs, Hyla chrysoscelis and H. versicolor, discriminate against synthetic 'calls' possessing a single interpulse interval 2-3 three times the optimal value, suggesting that ICNs are important for call recognition. The calls of H. versicolor consist of pulses that are longer in duration, rise more slowly in amplitude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…For instance, female Hyla chrysoscelis use pulse rate to recognize mates while Hyla versicolor females use pulse duration. These species preferences are reflected in differences in selectivity of interval-counting neurons and long-interval selective neurons in the inferior colliculus (Schul and Bush, 2002;Rose et al, 2015;Hanson et al, 2016). The X. laevis inferior colliculus is also populated by auditory neurons that respond preferentially to sound pulse rate (Elliott et al, 2011) and auditory sensitivity to temporal features of sound pulses could differ in X. petersii and X. victorianus.…”
Section: Divergence Of Vocal Patterns and Auditory Sensitivity Duringmentioning
confidence: 99%
“…For instance, female Hyla chrysoscelis use pulse rate to recognize mates while Hyla versicolor females use pulse duration. These species preferences are reflected in differences in selectivity of interval-counting neurons and long-interval selective neurons in the inferior colliculus (Schul and Bush, 2002;Rose et al, 2015;Hanson et al, 2016). The X. laevis inferior colliculus is also populated by auditory neurons that respond preferentially to sound pulse rate (Elliott et al, 2011) and auditory sensitivity to temporal features of sound pulses could differ in X. petersii and X. victorianus.…”
Section: Divergence Of Vocal Patterns and Auditory Sensitivity Duringmentioning
confidence: 99%
“…These neurons, described in multiple anuran species, are only responsive to signals with a minimum number of correctly spaced sound pulses; signals containing gaps reset the process of temporal integration (Edwards et al, 2002;Rose et al, 2015). Correspondingly, we found that stimuli containing gaps were highly unattractive to females.…”
Section: Temporal and Frequency Filters In The Nervous Systemmentioning
confidence: 53%
“…This component was identical to the 'typical H. versicolor' stimulus except that for every 3 pulses broadcast, 3 pulses were silenced. Temporal filters in the anuran auditory system are especially sensitive to gaps within calls, which reset the process of temporal integration (Henderson and Gerhardt, 2013;Rose et al, 2015;Schwartz et al, 2010). (5) Tone.…”
Section: Stimulus Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Such reductions in modulation depth were similar to structural changes that would yield declines in ΔV. These alterations could potentially attenuate the responses of interval-counting neurons in the auditory mid-brain of gray treefrogs (Rose et al 2015). Nevertheless, Kuczynski et al (2010) judged females fairly tolerant of drops in modulation depth, especially at lower signal amplitudes.…”
Section: Tests With Femalesmentioning
confidence: 95%